A Correlation between Upper Extremity Compressive Neuropathy and Nerve Compression Headache. Issue 6 (December 2021) - Gfrerer, Lisa; Chartier, Christian; Lans, Jonathan; Eberlin, Kyle R.; Austen, William Gerald
Abstract : Background: Compressive neuropathies of the head/neck that trigger headaches and entrapment neuropathies of the extremities have traditionally been perceived as separate clinical entities. Given significant overlap in clinical presentation, treatment, and anatomical abnormality, the authors aimed to elucidate the relationship between nerve compression headaches and carpal tunnel syndrome, and other upper extremity compression neuropathies. Methods: One hundred thirty-seven patients with nerve compression headaches who underwent surgical nerve deactivation were included. A retrospective chart review was conducted and the prevalence of carpal tunnel syndrome, thoracic outlet syndrome, and cubital tunnel syndrome was recorded. Patients with carpal tunnel syndrome, cubital tunnel syndrome, and thoracic outlet syndrome who had a history of surgery and/or positive imaging findings in addition to confirmed diagnosis were included. Patients with subjective report of carpal tunnel syndrome/thoracic outlet syndrome/cubital tunnel syndrome were excluded. Prevalence was compared to general population data. Results: The cumulative prevalence of upper extremity neuropathies in patients undergoing surgery for nerve compression headaches was 16.7 percent. The prevalence of carpal tunnel syndrome was 10.2 percent, which is 1.8- to 3.8-fold more common than in the general population. Thoracic outlet syndrome prevalence was 3.6 percent, with no available general population data for comparison. Cubital tunnel syndrome prevalence was comparable between groups. Conclusions: The degree of overlap between nerve compression syndromes of the head/neck and upper extremity suggests that peripheral nerve surgeons should be aware of this correlation and screen affected patients comprehensively. Similar patient presentation, treatment, and anatomical basis of nerve compression make either amenable to treatment by nerve surgeons, and treatment of both entities should be an integral part of a formal peripheral nerve surgery curriculum.